The Influence of Risk Perception on Visit Decision to Tourism Village: The Mediating Role of Tourist Motivation - Ketut Alit Ari Antari; Ni Ketut Wiwiek Agustina; Putu Gde Arie Yudhistira (Universitas Pendidikan Ganesha, 2023)
Community Tourism Village remains a favorite choice to visit despite the various risks threaten during the COVID-19 pandemic. This study aims to analyze the role of tourist motivation in mediating the influence of risk perceptions on visit decisions to Penglipuran Tourism Village, which still has a high number of tourist visits during the pandemic. The population in this study were domestic tourists, with a total sample of 400 obtained using the purposive sampling technique. The data analysis technique uses SmartPLS 4 by testing the validity, reliability, and mediating effect test on the research data. The results of the research data analysis show influence from each variable, with 47.0% of the variance of tourist motivation determined by risk perception, and 58.2% of the variance in visiting decisions was determined by risk perception and tourist motivation. Thus, tourist motivation positively and significantly mediates the risk perception in visiting decisions. This research can help tourism village managers and the government prepare and improve the services and facilities provided to become healthy, safe, and low-risk COVID-19 tourist destinations.